Mata: An Android Eye-Tracking Based User Interface Control Application - Yaya Heryadi; Michael James (Bina Nusantara University, 2016)
The advent of smartphone technology has provided us with intelligent devices for communication as well as playing game. Unfortunately, applications that exploit available sensors in the smartphone are mostly designed for people with no physical handicap. This paper presents Mata, a game user interface using eye-tracking to operate and control games running on Android smartphone. This system is designed to enhance user experiences and help motoric impaired peoples in using smartphone for playing games. Development and testing of the Mata system has proven the concepts of eye-tracking and eyegazing usage as unimodal input for game user interface.